PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN KEPUASAN KERJA TERHADAP PERILAKU KEWARGAAN ORGANISASI GURU SEKOLAH DASAR NEGERI KECAMATAN KRAS KABUPATEN KEDIR - Gunawan, Imam (Premiere Educandum, 2015)
The objective of this research is to found out the influence of transformational leadership and job satisfaction toward organizationalcitizenship behavior of the teacher in primary school Kras District of Kediri.This research used quantitative approach. The participants of the research are159 teachers of 30 primary school Kras, District of Kediri. The data foundusing closed model questionnaire instrument. The data analyzed using pathanalyzing, with the help of SPSS PASW Statistics 18 program. The results of theresearch show that there is a significance influence between transformationalleadership and job satisfaction toward organizational citizenship behavior ofthe teacher in primary school Kras, District of Kediri. The transformationalleadership contributes 15.1% while the job satisfaction contribution is 20.4%.Other variables beyond this research contribute 64.5%.Keywords: transformational leadership, job satisfaction, organizational citizenship behavior